Early swallowing testing in patients with post-stroke dysphagia: a systematic review - Martins, Rosa (2023)
Introduction: Early testing of swallowing in post-stroke patients, with prolonged use of a nasogastric tube (NGT), has proven to be very positive and with very significant health gains. Objective/s: To evaluate the benefits of early testing for dysphagia in people with a nasogastric tube after a stroke. Methods: Systematic literature review based on the method proposed by the Joanna Briggs Institute. Identification of the issue; literature search (2021/2022) using the B-on, CINAHL Complete, PubMed, Medline and Cochrane Library databases, resulting in 49 articles. After evaluating the studies, taking into account the defined selection criteria, a set of six articles resulted for data synthesis. Results: All studies demonstrate benefits of early testing for dysphagia in people with NGT after stroke. Studies have observed a decrease in aspiration pneumonia rates, a decrease in length of stay, improvements in functional capacity, less need for hospitalizations in long-term continuing care units after discharge, and a decrease in mortality rates. The evidence also highlighted the fact that the presence of NGT constitutes a predictor of complications. Conclusion: The benefits of early testing for dysphagia in post-stroke patients are effective, improving different dimensions of quality of life. Thus, the need emerges to establish intervention protocols for early screening of dysphagia in this type of patient, with regular and systematic evaluation. It is suggested that the implementation be carried out by specialized nurses, specifically nurses in rehabilitation.